Exosomal miRNA-16-5p Derived From M1 Macrophages Enhances T Cell-Dependent Immune Response by Regulating PD-L1 in Gastric Cancer - Li, Zhengtian; Suo, Bing; Long, Gang; Gao, Yue; Song, Jia; Zhang, Mengzhe; Feng, Baiyu; Shang, Ce; Wang, Dawei (Frontiers in Cell and Developmental Biology, 2020)
Macrophages have an affinity to developing tumors and have been shown to play a role in tumor combat and immune surveillance. However, the exact mechanism by which macrophages participate in the antitumor immune response remains unclear. Hence, the current study aimed to identify the effect of macrophages on GC cells via exosomes. Paired cancerous, tumor-adjacent, and noncancerous stomach tissues were initially from 68 GC patients. T cells were isolated from peripheral blood mononuclear cells (PBMCs) obtained from both the GC patients as well as the healthy donors. Next, the exosomes were isolated from LPS and IFN-γ-induced PBMCs (M1 macrophages) and co-cultured with human GC cells. Another co-culture system comprised of CD3+ T cells and exosomes-treated GC cells was then performed. BALB/c mice and NOD/SCID nude mice were prepared for effects of exosomal miR-16-5p on tumor growth and antitumor immune response in GC in vivo. A relationship between M1 macrophages and the poor survival of GC patients was identified, while they secreted exosomes to inhibit GC development and activate a T cell-dependent immune response. Our results revealed that miR-16-5p was transferred intercellularly from M1 macrophages to GC cells via exosomes and targeted PD-L1. M1 macrophage-derived exosomes containing miR-16-5p were found to trigger a T cell immune response which inhibited tumor formation both in vitro and in vivo by decreasing the expression of PD-L1. Taken together, the key findings of the current study suggest that M1 macrophage-derived exosomes carrying miR-16-5p exert an inhibitory effect on GC progression through activation of T cell immune response via PD-L1. Our study highlights the promise of M1 macrophages as a potential cell-based therapy for GC treatment by increasing miR-16-5p in exosomes.